2003
DOI: 10.1152/ajplung.00429.2002
|View full text |Cite
|
Sign up to set email alerts
|

PKA inhibits RhoA activation: a protection mechanism against endothelial barrier dysfunction

Abstract: Much evidence indicates that cAMP-dependent protein kinase (PKA) prevents increased endothelial permeability induced by inflammatory mediators. We investigated the hypothesis that PKA inhibits Rho GTPases, which are regulator proteins believed to mediate endothelial barrier dysfunction. Stimulation of human microvascular endothelial cells (HMEC) with thrombin (10 nM) increased activated RhoA (RhoA-GTP) within 1 min, which remained elevated approximately fourfold over control for 15 min. The activation was acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
160
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(183 citation statements)
references
References 46 publications
19
160
4
Order By: Relevance
“…However, thrombin did not activate Cdc42 in HUVEC, in contrast to one previous report that described a delayed activation of Cdc42 in immortalized human dermal microvascular endothelial cells 71. It is worth noting that the same immortalized cell line also does not display Rac1 inactivation in response to thrombin 82. When we modulated Rnd3 expression, thrombin‐induced inactivation of Rac1 was affected.…”
Section: Discussioncontrasting
confidence: 81%
“…However, thrombin did not activate Cdc42 in HUVEC, in contrast to one previous report that described a delayed activation of Cdc42 in immortalized human dermal microvascular endothelial cells 71. It is worth noting that the same immortalized cell line also does not display Rac1 inactivation in response to thrombin 82. When we modulated Rnd3 expression, thrombin‐induced inactivation of Rac1 was affected.…”
Section: Discussioncontrasting
confidence: 81%
“…In addition PG-induced activation of PKA may cause actin cytoskeletal remodeling by Rac-independent mechanisms, for example, via phosphorylation of myosin light chain kinase and reduction of its enzymatic activity [38,65], or via phosphorylation of Rho regulatory protein RhoGDI leading to Rho inhibition [21,38], or via PKA-mediated phosphorylation of vasodilator-stimulated phosphoprotein (VASP) leading to the structural relaxation of the actin cytoskeleton linked to tight junctions via VASP -ZO-1 complex, which result in enhanced endothelial barrier function [52]. Importantly, our studies revealed strong protective effects of PG in the pulmonary EC model of thrombininduced barrier hyperpermeability and in the murine model of ventilator-induced lung injury ( Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin binding to Gs-coupled EP2, EP4 and IP, which represent "relaxant" type of receptors leads to G sdependent activation of adenylate cyclase and elevation of intracellular cAMP levels [18]. Increases in intracellular cAMP levels have been associated with increased endothelial barrier integrity and linked to activation of PKA, which reduces endothelial MLCK activity, decreases pool of phosphorylated MLC, and leads to relaxation of actomyosin complex, stabilization of F-actin filaments and strengthening of cell-matrix adhesions [19][20][21][22]. In contrast, inhibition of basal cAMP/PKA activity increases pulmonary EC leak in part via activation of MAP kinase Erk1,2 [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no prior evidence of the direct phosphorPhosphorylation of phospholipase D1 and the m odulation of its interaction with RhoA by cAMP-dependent protein kinase ylation of PLD by PKA in vivo and in vitro has been presented. Moreover, direct involvement of the phosphorylations of RhoA and/or PLD in the inhibition of their association is not clearly understood although RhoA phosphorylation by PKA was shown to enhance or inhibit the association between RhoA and its binding proteins, such as Rho GDP dissociation inhibitor (RhoGDI) and Rho kinase (Lang et al, 1996;Dong et al, 1998;Forget et al, 2002;Ellerbroek et al, 2003;Qiao et al, 2003).…”
Section: Introductionmentioning
confidence: 99%